Design of a compliant adjustable constant-force gripper based on circular beams. (July 2022) - Gan, Jinqiang; Xu, Hao; Zhang, Xianmin; Ding, Huafeng
Abstract: Compliant grippers have been widely used in engineering systems to achieve precision operations. In this paper, a compliant adjustable constant-force gripper based on circular beams is developed for realizing the compatible and stable constant-force operation. In the developed gripper, a stiffness-combination constant-force mechanism (SCCFM) is applied as its basis. A pseudo-rigid-body PPRR model and particle swarm optimization algorithm are utilized for circular-beam modeling and identification of the SCCFM, respectively. A devised preload mechanism realizes the adjustment of the initial preloading state of the SCCFM. A series of experiments are conducted to demonstrate the effectiveness of the developed SCCFM and the gripper. Highlights: A compliant adjustable constant-force gripper based on circular beams is designed. A stiffness-combination constant-force mechanism is developed. A pseudo-rigid-body PPRR model is used for analyzing circular beams. A simple and effective two-way preload mechanism is proposed for the gripper.